Agricultura familiar: uma perspectiva da qualidade de vida do produtor rural orgânico da Paraíba - Pessoa, Yldry Souza Ramos Queiroz (2014)
Knowledge of quality of life is a very complex and rich in cultural and subjective dimensions, understood in a broad sense and multivariate theme. Considering the rural areas from agriculture, it is observed that the production standard defines significant changes in the environmental context and the quality of life of rural workers. To explain the relationship between quality of life and Family Organic Agriculture, we sought to analyze the quality of life of the organic family farmer, after change in agricultural management. The research, based on a procedure exploratory study supported the articulation theoretically constructed, showed their relevance and allowed to delimit with greater security, the central question of work. The WHOQOL - 100 treated the instrument of research on quality of life that directed the field study with organic farmers from the town of Lagoa Seca / PB. Farmers and family members are from rural regions Almeida, Alvinho, Lagoa de Barro, Lagoa Gravatá, Oiti and Pau Ferro. The average time is 39 years farming and organic family farm is 16 years. In the analysis work was found that the process of production of vegetables and fruits is divided into 08 steps and with respect to workloads observations showed the presence of: physical loads, mechanical stresses, psychological burden and ergonomic factors. Most farmers reported symptoms were fatigue and cramps in the legs . Regarding the quality of life was noticed that the Psychological Domain contributed positively to the quality of life with mean and standard deviation (17.83 ± 12.78) and Domain Environment negatively contributing to the quality of life of this group (9.00 ± 6.82). We conclude that the practice of Family Organic Agriculture should be seen as an effective strategy in promoting quality of life and social values in between, since it presents environmental sustainability with regard to life and socio-cultural diversity of populations